EFFECTIVENESS OF KELAKAI (STENOCHLAENA PALUSTRIS) EXTRACT ON THE HISTOLOGICAL LIVER ORGAN OF HARUAN SNAKEHEAD FISH (CHANNA STRIATA) AFTER AEROMONAS HYDROPHILA BACTERIAL INFECTION - Aminah; Fitriliyani I.; Fatmawati; Fauzana N.A.; Aisiah S.; Laishevtsev A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2024)
After being infected with A. hydrophila bacteria, haruan snakehead fish made efforts to restore their condition through recovery. The secondary metabolites found in kelakai leaves, namely alkaloid compounds, steroids, flavonoids, and iron, are believed to act as blood-boosting supplements. This study aims to analyze the histological response of the liver organs of haruan snakehead fish after being infected with A. hydrophila bacteria and fed with kelakai extract. The treatments provided for recovery were as follows: Treatment A (Control), Treatment B (50ml/kg Kelakai Extract), Treatment C (100ml/kg Kelakai Extract), and Treatment D (150ml/kg Kelakai Extract). The histological response of the liver organs of haruan snakehead fish with the addition of kelakai extract has been shown to effectively improve the histological structure of the liver post-infection with A. hydrophila bacteria, as indicated by an increase in the number of melanomacrophages.